GENERAL CONCEPT OF CULTURAL ETIQUETTE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Currently, there is a growing interest in a deep philosophical understanding of cultural ethics. At the same time, we understand that culture is not an attitude, not a situation, it cannot be tied to any social or political interests, but it expresses the essence of humanity. The article provides a detailed understanding of cultural ethics and its features.